A simplified complex torque coefficient method for analyzing and estimating the risk of multi-generator system subsynchronous resonance - Xin Zhao; Haixiang Xie; Xi Wu; Shan Gao; Ruoying Yu (International Journal of Electrical Power & Energy Systems)
The phenomenon of subsynchronous resonance (SSR) in multi-generator system is inherently complex and poses significant analytical challenges. This complexity arises primarily from the interactions among generators, particularly those sharing close torsional frequencies, which have not been sufficiently addressed. Moreover, the impact of these interactions on SSR remains inadequately explained. As a result, current SSR risk assessment methods often struggle to balance computational efficiency with modelling accuracy. In this paper, a simplified complex torque coefficient method is proposed, and an analytic formula for the generator’s electrical damping is derived for multi-generator system. This formula, which incorporates terms related to shaft dynamics, elucidates how rotor angle interactions affect damping characteristics and contribute to SSR. Based on these interactions and their dominant influencing factors, a systematic procedure is developed to assess SSR risk in multi-generator systems. The effectiveness of this evaluation procedure is validated through eigenvalue analysis and time-domain simulations. Compared to existing methods, the proposed approach offers improved suitability for practical power system applications.